Edukasi “CERVIBOOK” (Cerita Video dan Booklet) terhadap Kemampuan Kognitif dan Sikap Orangtua tentang Pencegahan Stunting pada Balita (STIKES dan AKZI Karya Husada Kediri, 2023)
Stunting is a disturbance of growth and development of children due to malnutrition. Stunting prevention can be done by parents, one of which is through cognitive abilities and attitudes. Cognitive abilities and attitudes of parents can be obtained through education from health workers. This study aims to determine the effect of educational